Monocyte/macrophages in innate immunity - Gordon, Siamon (Henry Stewart Talks, 2009)
Differentiation and distribution of macrophages, The EGF-TM7 family, Differentiation of monocytes, Tropic interactions, Monocyte recruitment, Immune activation, Monocyte heterogeneity, Differential activation of macrophage, Phagocytic pathway, APC pattern recognition receptors, APC receptors, Macrophage receptors and interactions, Dectin-1, Mannose receptor, MR ligands, Scavenger receptors, Neisseria Meningitidis, Receptor collaboration, Plasma membrane modulation of macrophage functions, Activatory and inhibitory receptor pairs, Macrophage fusion, Isolation of antibodies
Archived at 2017/10/16